2015
DOI: 10.1007/s00266-015-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mammaplasty Effect on Pulmonary Function and Arterial Blood Gas in the Overweight Female

Abstract: Overweight or obese women who underwent reduction mammaplasty showed significant improvements in certain PFT and all of the ABG measurements at 3 months after surgery. The more resected breast tissue predicts greater improvements in FEF 25-75 % and Sat O2, and greater reductions in BMI predicted increased improvements in FEF 25-75 % and FVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…In almost all studies, patients reported improvements in the vast majority of premorbid symptoms, a finding consistent with previous reviews of this subject (98). Other studies have also found that breast reduction had positive effects on depression and sexual function (99), as well as led to a significant improvement in lung function tests with a positive correlation between amount of breast tissue resected and improvement in expiratory capacity (100).…”
Section: Discussionsupporting
confidence: 80%
“…In almost all studies, patients reported improvements in the vast majority of premorbid symptoms, a finding consistent with previous reviews of this subject (98). Other studies have also found that breast reduction had positive effects on depression and sexual function (99), as well as led to a significant improvement in lung function tests with a positive correlation between amount of breast tissue resected and improvement in expiratory capacity (100).…”
Section: Discussionsupporting
confidence: 80%
“…Chest wall movement and therefore compliance may be restricted with increased weight on chest wall as in case of heavy weight breast. Thus, decreasing breast weight, would hypothetically improve ventilation and compliance of chest wall [5]. In the study of Cunha et al, restrictive effects of heavy breasts on the compliance of chest wall was discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Some insurance companies still limit and refuse payment for reduction mammaplasty, as it is still categorized as an aesthetic procedure. It is important economically to provide evidence of breast reduction surgery benefits to help decrease these limitations and support women in need of this procedure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Вопросы реконструктивной и пластической хирургии риск появления грыжи межпозвонкового диска и коррелирует с психологическими проблемами [12]. Затруднение дыхания является еще одним важным симптомом макромастии у здоровых женщин, хотя оно встречается реже, чем другие симптомы [13]. Макромастия также может являться фактором риска развития мастопатии [7].…”
Section: гипертрофия молочных железunclassified